Non-Renewable Resources, Fiscal Rules, and Human Capital - Levine, Paul; Melina, Giovanni; Onder, Harun (World Bank, Washington, DC, 2016)
This paper develops a multi-sector, small open economy Dynamic Stochastic General Equilibrium model, which includes the accumulation of human capital, built via public expenditures in education and health. Four possible fiscal rules are examined for total public investment in infrastructure, education, and health in the context of a sustainable resource fund: the spend-as-you-go, bird-in-hand spending; moderate front-loading, and permanent income hypothesis approaches. There are two dimensions to this exercise: the scaling effect, which describes the level of total investment, and the composition effect, which defines the structure of investment between infrastructure, education, and health. The model is applied to Kenya. For impacts on the non-resource economy, efficiency of spending, and sustainability of fiscal outcomes, the analysis finds that, although investment frontloading would bring high growth in the short term, the permanent income hypothesis approach is overall more desirable when fiscal sustainability concerns are taken into consideration. Finally, a balanced composition is the preferred structure of investment, given the permanent income hypothesis allocation of total investment over time.